2006
DOI: 10.1051/0004-6361:20054271
|View full text |Cite
|
Sign up to set email alerts
|

Multi-colour optical monitoring of eight red blazars

Abstract: Context. We present the observational results of multi-colour optical monitoring of eight red blazars from 2003 September to 2004 February. Aims. The aim of our monitoring is to investigate the spectral variability as well as the flux variations at short and long time scales. Methods. The observations were carried out using the 1.0 m robotic telescope of Mt. Lemmon Optical Astronomy Observatory, in Arizona, USA, the 0.6 m telescope of Sobaeksan Optical Astronomy Observatory and the 1.8 m telescope of Bohyunsan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
177
3
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(202 citation statements)
references
References 75 publications
21
177
3
1
Order By: Relevance
“…14, fast flares exhibited a strong bluerwhen-brighter (BWB) trend in inter-night variation (bottom panel), but it is messy in the intra-night variation (top panel). This is consistent with the common trend for blazars when they are in active states (Gu et al 2006;Wu et al 2007). According to Hu et al (2006), the colour results are not strongly affected by the host galaxy, since it has similar colours to the AGN.…”
Section: Colour Analysissupporting
confidence: 90%
“…14, fast flares exhibited a strong bluerwhen-brighter (BWB) trend in inter-night variation (bottom panel), but it is messy in the intra-night variation (top panel). This is consistent with the common trend for blazars when they are in active states (Gu et al 2006;Wu et al 2007). According to Hu et al (2006), the colour results are not strongly affected by the host galaxy, since it has similar colours to the AGN.…”
Section: Colour Analysissupporting
confidence: 90%
“…The source brightness was found to have strong BWB chromatism on intraday timescales. The BWB trend has been found to be predominant in BL Lacertae by all optical observations of this source till date during both flaring and steady states (Ghosh et al 2000;Gu et al 2006) which was revealed by our observations also. Villata et al (2004b) found that the intraday flares followed BWB trend strongly with a slope of ∼ 0.4 which is also the case for our data with the slopes of the intra-night LCs more than ∼ 0.4 in majority of cases.…”
Section: Colour-magnitude Relationshipsupporting
confidence: 83%
“…Optical observations can also indicate the possible presence of other components in addition to synchrotron continuum. There is good evidence for the presence of IDV and colour variability in some BL Lacertae objects and our source is among those (e.g., Carini et al 1992, Clements & Carini 2001, Gu et al 2006, H.E.S.S. Collaboration et al 2011).…”
Section: Introductionmentioning
confidence: 55%
“…A bluer-when-brighter behaviour was also detected by other authors in datasets more or less extended in time (e.g. Zhang et al 2004;Stalin et al 2006;Gu et al 2006).…”
Section: Introductionsupporting
confidence: 77%